The factors that influence practice of hibah within the Islamic estate planning in Malaysia / Nor Asfarina Mohamad Nor - Mohamad Nor, Nor Asfarina (Faculty of Business Management, 2018)
Islamic estate planning comprises of faraid, wasiyyah (bequest) and hibah. Practice on wasiyyah and hibah different on the time horizon and ruling of practice. However, there have some issue arises due to inefficiency on the management of estate planning. The most substantial issue is the registered name of land still do not change after the landlord passed away. A number of frozen estates because of the increasing income level and asset possession, and overlapping heirs that have to take such a long period to deal with bigger number of heirs. It happens because the attitude does not interest to the procedure to manage the estate distribution. Lack of interest neglected to make planning and unrealized the importance of estate planning that had given the difficulty to the heirs in managing the property. The objectives in this study to find out the relationship between knowledge, household income, religiosity, subjective norm and practice of hibah. The population of this study is Malaysian, and the sample is parents. Sampling technique is convenience sampling and using a questionnaire to collect the data. The sample size in this research is 150 respondents and data collected by online survey and by hand within one month. Finding on this research is relationship knowledge, religiosity and subjective norms are significant. Then, only household income has no significant relationship which is only had a small relationship on the practice of hibah.